Analysis of factors associated with arterial stiffness in the general working-age population - V. S. Kaveshnikov; I. A. Trubacheva; V. N. Serebryakova (Российский кардиологический журнал, 2022)
Aim. To examine associations of cardio-ankle vascular index (CAVI) with classical, behavioral and social risk factors (RFs) of cardiovascular disease (CVD) in adult population.Material and methods. The study included 1365 people (women, 59%) from a representative sample aged 25-64 years (ESSE-RF), who underwent standard cardiology screening and volume sphygmography (VaSera-1500). All respondents signed an informed consent to participate in the study. The analysis included blocks of classical, social and behavioral risk factors for CVD. A linear model was used to identify associations. An error rate of <5% was considered significant.Results. Age, sex, systolic blood pressure (SBP), triglycerides were associated with higher CAVI values, and body mass index (BMI) was associated with lower values, respectively. After 45 years, a direct association with heart rate (HR) became increasingly important, while after 50 years — with diabetes and the intake of beta-blockers, while the association between diabetes and CAVI was observed only among individuals not taking angiotensin-converting enzyme (ACE) inhibitors. A direct association was found with high-sensitivity C-reactive protein (hsCRP) in men, and an inverse association with diuretics in women, respectively. A sedentary work in combination with a history of bronchitis or with positive family history for CVD showed a direct relationship, while a sufficient physical activity (PA) showed an inverse relationship with the studied indicator, but only among people with belowaverage income.Conclusion. According to the data obtained, in addition to age and sex, the following risk factors made a significant contribution to CAVI parameters in the examined population: BMI, SBP, triglycerides, diabetes, HR, intake of betablockers, diuretics, ACE inhibitors; hsCRP, PA. The unfavorable role of betablockers, high HR, diabetes, sedentary work, chronic lung pathology, hereditary burden, as well as the protective role of ACE inhibitors, diuretics and intense PA in relation to arterial stiffness in the working-age population has been shown. Additional studies are needed to determine the nature of a number of associations. The results obtained may contribute to the study of CAVI role in risk stratification and further development of methodological approaches to CVD prevention.